2019
DOI: 10.18047/poljo.25.2.8
|View full text |Cite
|
Sign up to set email alerts
|

An overview on the use of hemp (Cannabis sativa L.) in animal nutrition

Abstract: The aim of the paper was to research the possibility of using hemp (Cannabis sativa L.) in animal nutrition. In animal nutrition, hemp seeds can be used, as well as hempseed cake, and hemp oil as supplement in feed mixtures. Hemp seeds are rich in crude protein and crude fat with adequate proportions of linoleic (LA, C18:2 n-6) and linolenic (ALA, C18:3 n-3) acid. The addition of hemp oil in diets of dairy goats increased milk fat with increasing conjugated fatty acid (CLA) and polyunsaturated fatty acids (PUF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The interest to this plant is mainly oriented to produce seed for human and animal nutrition, shives for construction (green building) and animal bedding, and fibre for textile and paper industry (“industrial hemp”). In dairy ruminant nutrition, hempseed and derivatives (oil, cake and meal) can be used as a supplement in feed mainly as sources of essential fatty acids and essential amino acids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest to this plant is mainly oriented to produce seed for human and animal nutrition, shives for construction (green building) and animal bedding, and fibre for textile and paper industry (“industrial hemp”). In dairy ruminant nutrition, hempseed and derivatives (oil, cake and meal) can be used as a supplement in feed mainly as sources of essential fatty acids and essential amino acids [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to linseed, hempseed supplementation offers a well-balanced linoleic acid/linolenic acid ratio of about 3:1 and contains both stearidonic acid (C18:4 n-3) and γ-linolenic acid (C18:3 n-6) [13]. The supplementation of ruminants' diet with hempseed and hempseed oil has been tested and a higher milk fat content with larger proportions of linoleic acid, rumenic acid (C18:2 cis-9, trans-11), and linolenic acid were observed in both sheep [14] and goats [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hemp seeds and hempseed cake contain tocopherols, especially γ-tocopherol (60.85 and 33.72 mg/100g DM, respectively), which increase oxidative stability of sheep milk (Mierlita, 2018). Klir et al (2019) indicated the possibility of using hempseed cake in animal diets without causing major changes in production and possible increase of desirable fatty acids in animal products.…”
mentioning
confidence: 99%